Melatonin improves hyperglycemia induced damages in rat brain. Issue 8 (13th September 2018) - Gurel‐Gokmen, Begum; Ipekci, Hazal; Oktay, Sehkar; Alev, Burcın; Ustundag, Unsal Velı; Ak, Esın; Akakın, Dılek; Sener, Goksel; Emekli‐Alturfan, Ebru; Yarat, Aysen; Tunali‐Akbay, Tugba
Abstract: Background: Diabetes mellitus is an endocrine disorder which is characterized by the development of resistance to the cellular activity of insulin or inadequate insulin production. It leads to hyperglycemia, prolonged inflammation, and oxidative stress. Oxidative stress is assumed to play an important role in the development of diabetic complications. Melatonin is the hormone that interacts with insulin in diabetes. Therefore, in this study, the effects of melatonin treatment with or without insulin were examined in diabetic rat brain. Methods: Rats were divided into five groups as control, diabetes, diabetes + insulin, diabetes + melatonin, and diabetes + melatonin + insulin. Experimental diabetes was induced by streptozotocin (60 mg/kg, i.p.). Twelve weeks after diabetes induction, rats were decapitated. Malondialdehyde, glutathione, sialic acid and nitric oxide levels, superoxide dismutase, catalase, glutathione‐S‐transferase, myeloperoxidase, and tissue factor activities were determined in brain tissue. Results: Melatonin alone showed its antioxidant effect by increasing brain glutathione level, superoxide dismutase, catalase, and glutathione‐S‐transferase activities and decreasing malondialdehyde level in experimental diabetes. Although insulin did not have a significant effect on glutathione and glutathione‐S‐transferase, its effects on lipid peroxidation, superoxide dismutase, and catalase were similar to melatonin; insulin also decreased myolopeoxidase activity and increased tissue factor activity. Combined melatonin and insulin treatment mimicked the effects of insulin. Conclusion: Addition of melatonin to the insulin treatment did not change the effects of insulin, but the detailed role of melatonin alone in the treatment of diabetes merits further experimental and clinical investigation.